Injectable gel loaded with periplaneta americana glycoprotein microspheres
By extracting glycoprotein microspheres from the American cockroach drug residue and combining with cationic guar gum to form an injectable gel, the problem of easy inactivation and poor adhesion of glycoprotein delivery in vivo is solved, and stable and controllable drug delivery and efficient resource reuse is achieved.
Patent Information
- Application Number
- CN202311332352.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to effectively solve the physical and chemical stability problems of the active ingredients in the American cockroach drug residue, which leads to easy deactivation during delivery in vivo, and poor adhesion during direct administration of the drug, making it difficult to control the drug release position and stability.
American cockrobin glycoprotein microspheres were obtained by alkaline alcohol deposition and macroporous resin purification processes, and combined with cationic guar gum hydroxypropyl trimethylammonium chloride, and an injectable gel was formed by ultrasonic dispersion and acid-base mixing.
It has achieved stable delivery of American cockroach glycoprotein, improved the controllability and stability of the drug in the body, and has good antibacterial effects and injectable performance, solving the problem of waste of drug residue resources.
Smart Images

Figure BDA0004494511740000081 
Figure BDA0004494511740000082 
Figure HDA0004494511750000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer medical materials, and in particular relates to a multifunctional injectable gel loaded with animal active ingredient microspheres and a preparation method thereof. Background Art
[0002] The American cockroach is the most widely used insect Chinese medicinal material. Its ethanol extract is the raw material for the production of Kangfuxin Liquid, Ganlong Capsule, Xinmailong Injection and other medicines. The upstream industries such as breeding and processing have developed rapidly in recent years. The amount of waste drug residues generated by this is increasing day by day. At present, the traditional methods of incineration, landfill, and fixed area stacking are still used for its treatment, which has a significant impact on the ecological environment and also increases the economic burden on enterprises. The development of new methods for the recycling and reuse of American cockroach drug residues and the downstream industrial chain has not received enough attention, resulting in serious waste of resources. After defatting and decalcification, the alcohol-extracted drug residues of American cockroach still contain 42.20% protein, and the content of other active ingredients such as polysaccharides and polyphenols is still considerable, so it has important development significance and economic value. More importantly, the wound healing, anti-inflammatory, antibacterial and antioxidant activities of American cockroach powder have been fully verified (Lu et al., Process Biochem., 2021, 110, 151-162), especially polysaccharides, peptides, proteins and their complexes - glycoproteins (Luo et al., Fitoterapia, 2014, 95, 115-120) have been shown to promote collagen production, granulation tissue production, promote cell proliferation, antibacterial and anti-acute inflammation activities (Zhu et al., Molecules, 2018, 23, 101). These characteristics are of great significance in the treatment of traumatic tissues in clinical practice, and also provide a basis for the development of more different wound healing and anti-inflammatory drugs in vivo.
[0003] Since proteins are often affected by pH and enzymes in body fluids, causing structural damage and even inactivation, it is particularly important to design drug delivery methods that can improve their physical and chemical stability. Microspheres can be embedded in solid or liquid drugs to protect them from damage; they have been found to be very suitable for delivering small molecule drugs, gene vaccines, stem cells and protein preparations. In addition, the microsphere system also has a good drug sustained release effect. On the other hand, due to their dispersibility, when they are directly applied to damaged skin or tissue, the microspheres often have poor adhesion and are easy to wander or even detach, making it difficult to control the location of drug application and ensuring effective and stable drug release. This shortcoming needs to be improved urgently.
[0004] In recent years, tissue engineering materials have made significant progress. Among them, hydrogel, as a water-swollen network of cross-linked hydrophilic polymers, usually has good compatibility with proteins, cells and tissues, and can provide a favorable microenvironment for cell survival and growth. Therefore, it is a material suitable for use as an artificial extracellular matrix in tissue engineering. On the other hand, injectable hydrogels formed in situ after injection at the treatment site have received widespread attention in the field of biomedical materials. Its advantage is that traditional implantation surgery can be replaced by a simple minimally invasive injection procedure. In addition, cells and bioactive molecules (such as growth factors) can be incorporated as needed, and the shape adaptability of the injectable gel allows it to maintain full integration with the surrounding irregular defective tissue.
[0005] Cationic guar gum (CG), as one of the guar gum derivatives, belongs to galactomannan in structure. It is an easily available and inexpensive polysaccharide that can be used to construct hydrogels with various functions. Compared with some polysaccharides that are difficult to dissolve in water (such as cellulose and chitosan), cationic guar gum can be directly dissolved in water and exhibits better solubility. In addition, the galactose units contained in its side chains can interact with water molecules, increase the viscosity of the system, and then induce gelation. At the same time, the quaternary ammonium groups on the molecular chain also give cationic guar gum hydrogels antibacterial properties. However, the formation process of CG-based hydrogels takes a long time (often more than 6 hours at room temperature) and the steps are cumbersome, which limits its rapid and large-scale preparation. To address this problem, it is necessary to establish a relatively simple and efficient method to obtain guar gum gels with ideal injectable, rheological and adhesive properties.
[0006] At present, some injectable gels for in vivo wound treatment have major problems such as complex formula and process, limited functions, unsatisfactory bioadhesion performance and degradability. Based on the above background, the present invention prepares an injectable guar gum gel loaded with American cockroach glycoprotein microspheres, which is designed to have multiple functions such as filling, wound healing, drug loading, and inhibition of microbial growth. It has a novel formula, simple preparation, good properties, and is easy to mass produce; at the same time, it solves the problem of easy inactivation of American cockroach glycoprotein in vivo delivery, improves the position controllability and stability of microsphere application, and has good antibacterial effect and injectability. More importantly, the alcohol-extracted drug residues of American cockroaches are reused through this approach, realizing the high-value development of insect medicinal resources. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing an injectable gel loaded with microspheres, wherein the basic components involved include American cockroach glycoprotein microspheres and cationic guar gum; the preparation process adopted is simple, the gel has comprehensive functions and stable properties, no special equipment is required for preparation, and it has good development and application prospects. In the implementation process, the glycoprotein in the American cockroach drug residue is first obtained by alkali extraction, alcohol precipitation and macroporous resin purification, and then prepared into microspheres with uniform particle size and combined with guar gum hydroxypropyltrimethylammonium chloride to form an injectable gel; this strategy fully utilizes the multiple functions of the active components of American cockroach in the field of biomedicine, and the related products realize the high-value utilization of waste resources. The good physical and chemical properties of microspheres and gels in the preparation link reflect obvious combined advantages, and the overall properties and sustained-release properties of the gel loaded with American cockroach glycoprotein microspheres are better than those of the gel directly loaded with glycoprotein under the same conditions, and it is expected to play a stable, reliable and long-lasting role in clinical applications. Overall, the gel developed by the present invention has good injectability, mechanical properties, rheological properties and degradability, and is easy to achieve large-scale preparation.
[0008] Technical solution: In order to achieve the above purpose, a method for preparing an injectable gel loaded with American cockroach glycoprotein microspheres is proposed:
[0009] The injectable gel loaded with American cockroach glycoprotein microspheres of the present invention is characterized in that the used glycoprotein is derived from the drug residues left after alcohol extraction of American cockroaches, and is obtained through alkali extraction, alcohol precipitation and macroporous resin purification processes.
[0010] The injectable gel loaded with American cockroach glycoprotein microspheres as described in claim 1 is characterized in that the American cockroach glycoprotein is prepared into stable microspheres by emulsification and sodium tripolyphosphate-glutaraldehyde two-step cross-linking method.
[0011] The injectable gel loaded with American cockroach glycoprotein microspheres as described in claim 1 is characterized in that the gel matrix used is guar gum hydroxypropyltrimethylammonium chloride.
[0012] The above-mentioned method for preparing an injectable gel loaded with American cockroach glycoprotein microspheres is characterized in that guar gum hydroxypropyltrimethylammonium chloride is used as a gel matrix, and the target gel product is formed by adding microspheres and then ultrasonically dispersing them, and then adding hydrochloric acid and sodium hydroxide in sequence and mixing them. The specific steps are:
[0013] (1) The American cockroach residue (100-120 mesh) after 95% alcohol extraction was heated to reflux at 60° C. for 0.5-1 hour with 2% NaOH solution as solvent; the extract was filtered and concentrated, and then precipitated with three times the volume of ethanol at 4° C. to obtain a crude glycoprotein;
[0014] (2) dissolving the crude glycoprotein in deionized water, purifying it through HP20 macroporous resin, eluting it with 2 to 3 column volumes of 70% ethanol, and concentrating and freeze-drying the eluate to obtain the glycoprotein;
[0015] (3) slowly adding a glycoprotein aqueous solution (2-6 mg / mL) to a Span80 / liquid paraffin solution and emulsifying for 30-60 min; then adding a 1-2 mg / mL sodium tripolyphosphate aqueous solution dropwise, and then adding a 0.5-2% glutaraldehyde aqueous solution, and reacting for 1-2 hours; filtering the solidified microspheres, washing them twice with petroleum ether and ethanol respectively, freeze-drying them and storing them at low temperature;
[0016] (4) ultrasonically dispersing the glycoprotein microspheres (10-30 mg) obtained in (3) and guar gum hydroxypropyltrimethylammonium chloride powder in deionized water, adding 1-3% HCl solution and stirring evenly; then adding 0.2-0.4 mol / L NaOH solution, mixing evenly to obtain an injectable gel;
[0017] (5) The prepared gel is sterilized by ultraviolet light, and then sealed and packaged. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more completely illustrate the technical solution of the specific embodiment of the present invention, the following briefly describes the drawings required in the embodiment. The drawings described are only part of the embodiment of the present invention. For those skilled in the art, it should be possible to obtain other drawings of the embodiment based on these drawings. Among them:
[0019] Figure 1 is a Fourier transform infrared spectrum (FT-IR) of the glycoprotein described in the present invention;
[0020] Figure 2 The scanning electron microscope morphology (SEM) and particle size distribution diagram of the glycoprotein microspheres described in the present invention (a is the microsphere MS-6 prepared with 6 mg / mL glycoprotein; b is its particle size distribution diagram);
[0021] Figure 3 Zeta potential diagram of the glycoprotein microspheres described in the present invention (MS-2, MS-4, and MS-6 refer to microspheres prepared from glycoprotein solutions with concentrations of 2, 4, and 6 mg / mL, respectively);
[0022] Figure 4The rheological and self-healing characteristics of the glycoprotein microsphere gel described in the present invention are shown in Figure 1 (a is an oscillation amplitude sweep test of the gel loaded with MS-6 at an angular frequency of 5 rad / s; b is an oscillation frequency sweep test of the gel under a shear strain of 0.1%; c is a structural destruction and reconstruction curve of the gel at a constant angular frequency of 5 rad / s, under alternating shear strains of 1% and 400%, and a period of 60 s);
[0023] Figure 5 It is the in vitro degradation behavior of the glycoprotein microsphere gel described in the present invention (MS-2-gel, MS-4-gel, MS-6-gel refer to the gel loaded with MS-2, MS-4, MS-6 microspheres, respectively). DETAILED DESCRIPTION
[0024] The following is a detailed description of the present invention. Although specific embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0025] Example 1
[0026] The American cockroach residue (120 mesh) after 95% alcohol extraction was heated to reflux at 60°C for 1 hour with 2% NaOH solution as solvent; the extract was filtered and concentrated, and then precipitated with three times the volume of ethanol at 4°C to obtain a crude glycoprotein; the crude glycoprotein was dissolved in deionized water, purified by HP20 macroporous resin, eluted with 70% ethanol in 3 times the column volume, and the eluate was concentrated and freeze-dried to obtain the product glycoprotein, which was then tested by Fourier transform-infrared spectroscopy (FT-IR) with potassium bromide tablets. The results are as follows: Figure 1 As shown. Among them, 3442cm -1 The strong absorption peak is caused by the stretching vibration of OH and NH, and the absorption peak becomes broad due to the formation of intermolecular or intramolecular hydrogen bonds by hydroxyl groups, 2923cm -1 The signal at 1665cm is the CH stretching vibration absorption peak, which is a typical absorption peak of polysaccharides. -1 The strong peak at 1390 cm-1 corresponds to the stretching vibration of C=O in the amide group (amide I peak). -1 The stretching vibration of the amide group CN (amide III peak) at 1153 cm -1 and 1005cm -1 The absorption peak at 880 cm indicates the presence of pyranoside in the extracted polysaccharide. -1 There is an obvious absorption peak at , indicating the existence of β-glycosidic bond. All the above spectral signals suggest that the obtained product is glycoprotein.
[0027] Example 2
[0028] Take the glycoprotein solution (2 mg / mL) and slowly add it dropwise to the Span80 / liquid paraffin solution and emulsify for 30 minutes; then add 1 mg / mL sodium tripolyphosphate aqueous solution dropwise, and then add 0.5% glutaraldehyde aqueous solution, and react for 1 hour; filter the solidified microspheres, wash twice with petroleum ether and ethanol respectively, freeze-dry and store at low temperature.
[0029] Example 3
[0030] The glycoprotein solution (4 mg / mL) was slowly added dropwise to the Span80 / liquid paraffin solution and emulsified for 45 min; then a 1.5 mg / mL sodium tripolyphosphate aqueous solution was added dropwise, followed by a 1% glutaraldehyde aqueous solution, and the reaction was continued for 1.5 hours; the solidified microspheres were filtered, washed twice with petroleum ether and ethanol respectively, freeze-dried and stored at low temperature.
[0031] Example 4
[0032] The glycoprotein solution (6 mg / mL) was slowly added dropwise to the Span80 / liquid paraffin solution and emulsified for 60 min; then a 2 mg / mL sodium tripolyphosphate aqueous solution was added dropwise, followed by a 2% glutaraldehyde aqueous solution, and the reaction was continued for 2 h; the solidified microspheres were filtered, washed twice with petroleum ether and ethanol respectively, freeze-dried and stored at low temperature.
[0033] The microspheres prepared in Example 4 were observed by SEM. The microspheres prepared with a 6 mg / mL glycoprotein solution were named MS-6. The specific experimental operation was as follows: the microspheres were dispersed in ethanol and then dropped onto a silicon wafer for electron microscopy observation. The silicon wafer was then freeze-dried and sprayed with gold for SEM observation. Figure 2 As shown in the SEM image, the microspheres of MS-6 are full in shape, smooth in surface, good in roundness and uniformity, and there is no adhesion between the microspheres. Through the particle size distribution analysis of MS-6 microspheres, its particle size is mainly distributed around 1.22μm, and the distribution is relatively narrow.
[0034] The microspheres prepared in Examples 2, 3, and 4 were subjected to Zeta potential measurement. The specific experimental operation was as follows: a nanoparticle size and Zeta potential analyzer was used to determine the zeta potential of the three microspheres. Before the analysis, the prepared microspheres were dispersed in a pH 7.4 phosphate buffer at a concentration of 0.001% (w / v), and the pH values of these samples were adjusted to a range of 3.0-10.0 using 0.1 mol / L HCl or 0.1 mol / L NaOH. The results are shown in FIG. Figure 3As shown in the figure, the zeta potential of the three microspheres is 0 at a pH of about 5.6, indicating that the surface charge of the cross-linked microspheres is similar and the structure is similar. At alkaline pH, the absolute value of the zeta potential of MS-6 is higher than that of MS-4 and MS-2, indicating that a high microsphere concentration is helpful in preparing more stable microspheres, and the potential value of -31.1 mV of MS-6 confirms that it has good stability and is not easy to aggregate in suspension.
[0035] Example 5
[0036] MS-2 glycoprotein microspheres (10 mg) and guar gum hydroxypropyltrimethylammonium chloride powder were ultrasonically dispersed in deionized water, and 1% HCl solution was added and stirred evenly; then 0.2 mol / L NaOH solution was added and mixed evenly to obtain an injectable gel. The obtained gel was sterilized by irradiating with ultraviolet light for 60 minutes and then sealed for storage.
[0037] Example 6
[0038] MS-4 glycoprotein microspheres (20 mg) and guar gum hydroxypropyltrimethylammonium chloride powder were ultrasonically dispersed in deionized water, and 2% HCl solution was added and stirred evenly; then 0.3 mol / L NaOH solution was added and mixed evenly to obtain an injectable gel. The obtained gel was sterilized by irradiation with ultraviolet light for 60 minutes, and then sealed and stored and packaged.
[0039] Example 7
[0040] MS-6 glycoprotein microspheres (30 mg) and guar gum hydroxypropyltrimethylammonium chloride powder were ultrasonically dispersed in deionized water, and 3% HCl solution was added and stirred evenly; then 0.4 mol / L NaOH solution was added and mixed evenly to obtain an injectable gel. The obtained gel was sterilized by irradiating with ultraviolet light for 60 minutes and then sealed for storage.
[0041] The MS-6 microsphere-loaded gel (MS-6-gel) prepared in Example 7 was subjected to rheological testing. The specific steps were as follows: the gel was made into a cylindrical sample with a diameter of 2.5 cm and a height of 1.0 cm, the sample was placed in a rotational rheometer, and oscillation amplitude scanning, oscillation frequency scanning and alternating strain scanning tests were performed respectively, and the changes in storage modulus (G′) and loss modulus (G″) with angular frequency were recorded. The results are shown in FIG. Figure 4As shown in (a), in the oscillation amplitude scanning test with an angular frequency of 5.0 rad / s, within the strain range of 0.1% to 1000%, the G' and G" values of the MS-6-gel gel sample have an intersection. When the gel is subjected to a strain of 2.21%, G' suddenly drops below G", indicating that the hydrogel network structure is damaged and broken. It also shows that the network structure of the guar gum gel loaded with microspheres can withstand greater stress, and the structure will only be destroyed under a stress greater than 2.21%. Figure 4 In (b), under a constant shear strain of 0.1%, as the frequency changes, the G′ of the MS-6-gel is always greater than G″, indicating that the gel is always in a solid state, that is, the internal elastic network structure of the hydrogel is stable. From the rheological properties characterization results, it can be seen that this microsphere-loaded injectable hydrogel has excellent mechanical properties and structural stability. The self-healing ability of the MS-6-gel was evaluated by alternating strain sweep tests (see Figure 4 (c)). Under small strain (1%), G' of the hydrogel is greater than G", indicating that the gel remains in a gel state, while under large strain (400%), the value of G' is less than G", which means that the gel structure is destroyed and shows liquid-like viscous behavior. When the large strain is removed, G' can return to its original value, showing the good self-healing ability of the hydrogel. The formation of hydrogen bonds between the same-side hydroxyl groups in the guar gum mannose main chain structure is the main reason for the self-healing property.
[0042] The gel loaded with MS-6 microspheres prepared in Example 7 (MS-6-gel) was subjected to a release kinetics study, specifically comprising the following steps: 2 g of the prepared MS-6-gel was immersed in 30 mL of PBS solution (pH=7.4), incubated at 37°C for 24 hours, sampled 0.5 mL every hour, centrifuged the sample at 8000 rpm for 10 min, and the protein content released was determined by the Coomassie brilliant blue method, with the gel directly loaded with American cockroach glycoprotein as a control. The results showed that the gel directly loaded with American cockroach glycoprotein had reached the maximum cumulative release of glycoprotein (77.49%) at 8 h, and the release amount was significantly higher than that of the microsphere gel group in the 0-2 hour stage, such as 22.51% and 3.69% in 2 hours, respectively, indicating that there was a burst release phenomenon. The drug release of the gel (MS-6-gel) loaded with MS-6 microspheres has an obvious sustained-release effect. The cumulative release amount is less than 10% in the 0-4 hour stage, only 23.42% at 8 hours, and reaches 73.35% after 20 hours, showing a slow and long-lasting drug release behavior.
[0043] The gels prepared in Examples 5, 6, and 7 were subjected to an in vitro degradation test. The specific steps were as follows: 1.0 g of gel sample (W0) was immersed in 100 mL of simulated body fluid (containing 142 mM Na + ,5mM K+ ,1.5mM Mg 2+ ,2.5 mM Ca 2+ ,148.8mM Cl - ,4.2mMHCO3 - ,1mM HPO4 2- ,0.5mM SO4 2- , pH 7.4), which was changed once a day and shaken in a shaker at 60 rpm and 37 ° C. Samples were collected by centrifugation every 24 h, washed three times with ultrapure water, and finally dried and weighed (W t ). The weight reduction percentage WL (%) is calculated by the following formula:
[0044] The in vitro degradability of the samples was evaluated by measuring weight loss in a simulated physiological environment. Figure 5 As shown, during the test period, the weight of all samples gradually decreased over time. MS-4-gel and MS-2-gel degraded by about 79% and 74% respectively after 7 days, while MS-6-gel degraded by only about 57% after 7 days; the difference in degradation between the groups may be related to the cross-linking density. The above results show that the prepared gel exhibits excellent degradability.
[0045] The gels prepared in Examples 5, 6, and 7 were subjected to an inhibition zone test, and the specific method was referred to GB / T39101-2020. The commercial chitosan gel was used as the control group, and the inhibition zone test results of the gels loaded with different microspheres on Staphylococcus aureus and Escherichia coli are shown in the following table:
[0046]
[0047] From the data in this table, it can be seen that MS-6-gel has better antibacterial effects on both bacteria than other gels, indicating that the prepared new gel has ideal bactericidal properties; and the inhibitory effect on Gram-negative bacteria represented by Escherichia coli is better than that on Gram-positive bacteria represented by Staphylococcus aureus. The reason is that the cell wall of the former is composed of a thin layer of peptidoglycan and lipopolysaccharide, and lacks hardness and strength overall, making it vulnerable to antibacterial materials.
Claims
1. An injectable gel loaded with American cockroach glycoprotein microspheres, characterized in that: The core composition includes American cockroach glycoprotein microspheres and guar gum hydroxypropyltrimonium chloride.
2. The injectable gel loaded with American cockroach glycoprotein microspheres according to claim 1, characterized in that: The glycoprotein used comes from the drug residue left after alcohol extraction of American cockroaches, and is obtained through alkali extraction, alcohol precipitation and macroporous resin purification processes.
3. The injectable gel loaded with American cockroach glycoprotein microspheres according to claim 1, characterized in that: The glycoprotein of American cockroach was prepared into stable microspheres by emulsification and sodium tripolyphosphate-glutaraldehyde two-step cross-linking method.
4. The injectable gel loaded with American cockroach glycoprotein microspheres according to claim 1, characterized in that: The guar gum hydroxypropyltrimethylammonium chloride is used as a gel matrix, and the target gel product is formed by adding microspheres, performing ultrasonic dispersion, and then sequentially adding hydrochloric acid and sodium hydroxide and mixing.
5. The injectable gel loaded with American cockroach glycoprotein microspheres according to claim 1, characterized in that: The specific operations are: (1) The American cockroach residue (100-120 mesh) after 95% alcohol extraction was heated to reflux at 60° C. for 0.5-1 hour with 2% sodium hydroxide solution as solvent; the extract was filtered and concentrated, and then precipitated with three times the volume of ethanol at 4° C. to obtain a crude glycoprotein; (2) dissolving the crude glycoprotein in deionized water, purifying it through HP20 macroporous resin, eluting it with 2 to 3 column volumes of 70% ethanol, and concentrating and freeze-drying the eluate to obtain the glycoprotein; (3) slowly adding a glycoprotein aqueous solution (2-6 mg / mL) to a Span80 / liquid paraffin solution and emulsifying for 30-60 min; then adding a 1-2 mg / mL sodium tripolyphosphate aqueous solution dropwise, and then adding a 0.5-2% glutaraldehyde aqueous solution, and reacting for 1-2 hours; filtering the solidified microspheres, washing them twice with petroleum ether and ethanol respectively, freeze-drying them and storing them at low temperature; (4) ultrasonically dispersing the glycoprotein microspheres (10-30 mg) obtained in (3) and guar gum hydroxypropyltrimethylammonium chloride powder in deionized water, adding 1-3% hydrochloric acid solution and stirring evenly; then adding 0.2-0.4 mol / L sodium hydroxide solution, mixing evenly to obtain an injectable gel; (5) The prepared gel is sterilized by ultraviolet light, sealed and stored, and then packaged.